2002
DOI: 10.1128/aac.46.4.971-976.2002
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Activities of a Novel Cephalosporin, BMS-247243, against Methicillin-Resistant and -Susceptible Staphylococci

Abstract: The recent emergence of methicillin-resistant Staphylococcus aureus (MRSA) with decreased susceptibility to vancomycin has intensified the search for alternative therapies for the treatment of infections caused by this organism. One approach has been to identify a ␤-lactam with improved affinity for PBP 2a, the target enzyme responsible for methicillin resistance in staphylococci. BMS-247243 is such a candidate, with MICs that inhibit 90% of isolates tested (MIC 90 s) of 4, 2, and 8 g/ml for methicillin-resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…[2][3][4][5][6] With the increase in resistance of bacteria to antibiotic treatment, attention was given on developing novel approaches to antimicrobial therapy. [7][8][9][10][11][12][13] We have previously reported the significant antifungal activity of a series of sulfonamide-1,2,4-triazole derivatives against a series of micromycetes, compared to the commercial fungicide bifonazole. These compounds have also shown a comparable bactericidal effect to that of streptomycin but better activity than chlorampenicol respectively against various bacteria.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] With the increase in resistance of bacteria to antibiotic treatment, attention was given on developing novel approaches to antimicrobial therapy. [7][8][9][10][11][12][13] We have previously reported the significant antifungal activity of a series of sulfonamide-1,2,4-triazole derivatives against a series of micromycetes, compared to the commercial fungicide bifonazole. These compounds have also shown a comparable bactericidal effect to that of streptomycin but better activity than chlorampenicol respectively against various bacteria.…”
mentioning
confidence: 99%
“…The beta-lactam antibiotics that are used clinically do not bind to PBP 2a at therapeutic concentrations and therefore lack efficacy against infections caused by methicillin-resistant staphylococci. With the solution of the crystal structure of a soluble derivative of PBP 2a, low-affinity binding can be attributed at least in part to an energetically unfavorable acylation reaction of the active site serine due to the slippage of the beta-lactam molecule within a long groove that serves as the initial, reversible binding site in the formation of the Michaelis-Menten complex (16).Several cephalosporin and carbapenem derivatives that bind to PBP 2a with 100-fold or higher affinities than those of other beta-lactams and which are active in vitro and in vivo against methicillin-resistant staphylococci have been synthesized (2,6,7,13,20). These compounds have in common a relatively extended side chain attached to the ␣ ring of the beta-lactam compound core (3, 16).…”
mentioning
confidence: 99%
“…Several cephalosporin and carbapenem derivatives that bind to PBP 2a with 100-fold or higher affinities than those of other beta-lactams and which are active in vitro and in vivo against methicillin-resistant staphylococci have been synthesized (2,6,7,13,20). These compounds have in common a relatively extended side chain attached to the ␣ ring of the beta-lactam compound core (3, 16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to have activity against a wide range of clinical isolates (1,7,12,34), and in particular, garenoxacin has been shown to have good activity against Staphylococcus aureus, both methicillin sensitive and resistant (6), and the respiratory pathogens Streptococcus pneumoniae (26), Haemophilus influenzae, and Moraxella catarrhalis (8). The activity of garenoxacin has been further assessed against strains of S. aureus with specific topoisomerase mutations (21), and more recently, it has been shown that garenoxacin has similar potency against both topoisomerase IV and gyrase (16) (dual-targeting quinolone), thus requiring mutations in both topoisomerases for resistance to occur (29).…”
mentioning
confidence: 99%